Effect of systemic anticoagulant (acetyl-salicylic acid) application on implant osseointegration in rat tibias in allogeneic bone transplantation - Gul, Mehmet; Tanrisever, Murat; Dogan, Delil; Guney, Merve; Istek, Ozmen; Can, Koray; Dundar, Serkan (Univ Zulia, Facultad Ciencias Veterinarias, 2026)
The aim of this study is to investigate the effect of systemic administration of acetylsalicylic acid, used in the treatment of coronary artery disease, on the level of osseointegration of titanium implants in the transplanted bone in the treatment of bone defects created in rat tibias using allogeneic bone transplantation. Forty-two female Sprague Dawley rats, aged 6-12 months, were used in this study. The average weight of the rats used in this experimental study was between 270 and 300 grams. To prevent harm to the animals during the experiment, temperature was constantly controlled, and a 12-hour light/12-hour dark cycle was implemented. Among the groups without allo-graft, the mean bone-implant contact value was 6.31 (Median: 6.30) in the control group, while the value was 6.40 (6.20) in the Acetylsalicylic Acid dose 1 group. No significant difference was found between these two groups. In the Ac-etylsalicylic Acid dose 2 group, the value of 6.51 (6.80) was obtained, while an increase was observed compared to the control and Acetylsalicylic Acid dose 1 groups, but no significant difference was obtained. In this study the results demonstrated the beneficial effects of Acetylsalicylic Acid. Higher bone-to-implant fusion rates were achieved in the Acetylsalicylic Acid-treated groups. It is concluded that Acetylsalicylic Acid use may be beneficial in cases requiring bone augmentation.
Efecto de la aplicación de anticoagulante sistémico (ácido acetilsalicílico) en la osteointegración de implantes en tibias de rata en trasplante óseo alogénico
Keywords: Acetylsalicylic acid; allogeneic bone; osseointegration; bone implant connection